Pengembangan Waroeng Semawis Dalam Mendukung Wisata Kuliner Di Kota Semarang Provinsi Jawa Tengah - Sherdianto, Gayuh; Anom, I Putu (JURNAL DESTINASI PARIWISATA, 2019)
The selection of this research topic is based on the seriousness of Semarang City Government to maximize the potential of culinary tourism. The development of culinary tourism is expected to support the existing tourism in Semarang City . In this study , the researchers chose WaroengSemawis as the main focus of the research location. WaroengSemawis is a culinary night market located in the Chinatown area in ??Semarang City. Initially , WaroengSemawis was just a Lunar New Year Semawis Market held only days before the Lunar New Year day , but since 2004 WaroengSemawis became a regular event every weekend. There are many types of culinary available there, ranging from local cuisine to typical Chinese cuisine. In addition , there are also many historical Chinese temple s surround ing WaroengSemawis area that have their own history as well.                                 The purpose of this research is to analyze the potential of culinary tourism and the development strategy of the culinary tourism particularly at WaroengSemawis in Semarang City. The data used i in this i research i is the i type i of qualitative i i data, while i the i data i source i is i primary i data i and i secondary i i data. Data collection is done by observation, interview, literature study, and documentation. Data analysis technique used in this study is SWOT to find out what strategies can be used. The results of this study indicate that there are still some shortcomings that must be developed by the management of WaroengSemawis. The need of additional public toilets, parking lots, as well as the addition of traditional culinary or culinary types of Semarang. By increasing some of these facilities, it can help boosting the amenity and interest of tourists to visit WaroengSemawis so that it can leave a good impression on the tourists. Keywords: Development Strategy, Culinary Tourism, Waroeng Semawis